Transformasi Pendidikan di Era Digital: Dampak, Tantangan, dan Peluang dalam Dinamika Pembelajaran Mahasiswa di Lingkungan Perguruan Tinggi - Hapsari, Nandita Suri; Suranto, Suranto (PAKAR Pendidikan, 2025)
This study aims to explore the impact of educational transformation in the digital era on students during the learning process and the dynamics of education at the university level. A qualitative approach is used to collect data from FKIP students of Universitas Muhammadiyah Surakarta. Data collected from interviews and observations will be analyzed using the thematic analysis method, which identifies, analyzes, and reports relevant patterns or key themes relating to the challenges and opportunities faced by students in educational transformation. Thematic analysis is conducted interactively, with data grouped into thematic categories to identify key relationships and patterns relating to challenges and opportunities in digital education. This research will provide valuable insights into how the role of digital technology in education affects the dynamics of student learning and the implications for providing education that is more adaptive and responsive to individual needs. Digital education has great potential to not only increase flexibility in learning time and location but also enable the development of age-relevant skills, such as technological literacy, online collaboration, and critical thinking. Educational institutions play a key role in supporting this transformation, particularly through investment in adequate infrastructure and reliable internet access, as well as ongoing training for educators to increase capacity in digital learning management.